Lithuanian Place Names with the Stem “totor-” - Mickienė, Ilona; Baranauskienė, Rita (Respectus Philologicus, 2025)
Lithuania’s Tatars are amongst the oldest national minorities in the country. Culturally and ethnically different from the dominant majority of Lithuania’s population, this group have preserved their distinct customs, traditions, national and religious identity. Lithuania’s Tatar minority continues to be the subject of diverse academic studies, focusing on various aspects such as the status of this community in the 19th century (Bairašauskaitė, 1996), the oldest Tatar manuscripts (Miškinienė, 2001), the Tatar history and culture (Jakubauskas et al., 2009), female Tatar anthroponyms in 16–17th century Lithuania (Čirūnaitė, 2021). This research aims to analyse the structure and territorial spread of toponyms with the stem totor-, confirming the areas members of this community have inhabited in the past or continue to inhabit today. The structural analysis of toponyms with the stem totor- revealed the dominance of secondary place names derived from the ethnonym totorius (Tatar), personal name Totorius or another place name with the same stem. The most significant number of Tatars have historically inhabited the southern (south-eastern and south-western) and the northern parts of Lithuania.